A comparative evaluation of the variations on the shades of pressable ceramic system with the layering technique after different number of firing cycles: An in vitro study - Manupreet Kaur; Shailendra Kumar Sahu (Wolters Kluwer Medknow Publications, 2024)
Aim: The main aim of the present study was to compare and evaluate the effect of repetitive firings on different shades of a pressable all ceramic system layered with veneering porcelain. Setting and Design: In-vitro comparative study Materials And Methods: An in vitro comparative study was conducted, and a total of 60 disc shaped specimens (15 mm in diameter and 0.8 mm in thickness) were made of heat pressed ceramic of shades A2, A3, and B2 (20 discs of each shade) grouped as Group I, II, and III, respectively, using the lost wax technique. The discs were subsequently layered with veneering porcelain followed by glazing and overglazing and underwent a firing cycle at each step until six times combined. CIE L*a*b* measurements were noted on each sample after the third, fourth, fifth, and sixth firing using VITA Easyshade Advance 4.0 spectrophotometer. Statistical Analysis Used: Statistical Analysis was done by SPSS 17.0 software. One way analysis of variance, multiple comparisons using the Tukey test, and descriptive statistical analysis were done for all the groups in the study. P <0.05 was statistically significant. Results: The mean color differences for the repeated firings were imperceptible (ΔE <1.67) to the human eye for all ceramic samples tested except between the fourth and fifth firing of Group II (shade A3). Conclusion: The analysis revealed that although repeated firings lead to changes in L*, a*, and b* values, the mean color difference was below the clinically acceptable color change (ΔE <3.7).